Utility of imaging modalities for predicting carcinogenesis in lobular endocervical glandular hyperplasia. - Makiko Omori; Tetsuo Kondo; Hikaru Tagaya; Yumika Watanabe; Hiroko Fukasawa; Masataka Kawai; Kumiko Nakazawa; Akihiko Hashi; Shuji Hirata (PLoS ONE, 2019)
Objectives To investigate the use of imaging methods for predicting carcinogenesis in lobular endocervical glandular hyperplasia (LEGH). Methods We retrospectively analyzed preoperative images on transvaginal sonography and magnetic resonance imaging (MRI) in 23 cases with histologically diagnosed LEGH. Results Shape of cervical multicystic lesions on MR images could be divided into two types the flower-type with many small cysts surrounded by larger cysts, and the raspberry-type with many tiny, closely aggregated cysts. Six (46%) of 13 cases had raspberry-type lesions that were not detected on transvaginal sonography but were seen on MRI. Adenocarcinoma in situ (AIS) was identified in 4 postmenopausal women with raspberry-type lesions during the follow-up periods. In these cases, cytologic examination by targeted endocervical sampling using sonography enabled early detection of AIS. Conclusions MRI and cytologic examination by targeted endocervical sampling may be very useful for predicting carcinogenesis in LEGH.